Wave forecast investigations on downscaling, source terms, and tides for Aotearoa New Zealand - R. Santana; R. Santana; R. Gorman; E. Lane; S. Moore; C. Bosserelle; G. Reeve; C. Rautenbach; C. Rautenbach (Geoscientific Model Development)
This study evaluates the effects of downscaling, source terms, and tidal interactions on numerical wave forecasts in Aotearoa New Zealand. We utilised a set of three nested domains (from global to regional scale) to examine significant wave height (Hs), first-order mean period (Tm01), and peak wave direction at two coastal locations, Banks Peninsula and Baring Head. Downscaling markedly improved forecast accuracy at Baring Head, a tidally constricted region, reducing Hs forecast error by 28 %. However, improvements at Banks Peninsula were minimal, likely due to its open-coast characteristics, which are adequately represented even by lower-resolution models. This variability was also evident in the Tm01 predictions, with notable improvements in bias reduction through model downscaling, particularly at Baring Head. Using default source term 6 (ST6) parameters generally improved Hs predictions on the west coast but worsened them on the east, indicating a geographical dependency in model performance. Tidal forcing had a small impact on the overall forecast skill, and its impact was mostly noticed at Baring Head, where tides force large variability. However, the tidally driven wave model showed smaller 12 h variability compared to observations. The study underscores the importance of tailored modelling approaches that consider local geographical and hydrodynamic conditions to optimise wave forecasting.